PENGARUH EPERIENTIAL MARKETING TERHADAP BRAND AWARENESS SERTA DAMPAKNYA PADA MINAT BELI (STUDI PADA PRODUK SMARTPHONE SAMSUNG ELECTRONIC INDONESIA CABANG PEKANBARU - Syuhada, Muhammad; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of experiential marketing on brand awareness as well as their impact on buying interest (Study on smartphones, Samsung Electronic Indonesia branches pekanbaru). This research method in this research is quantitative with program SPSS, where samples were used that visitors to the store as many as 100 respondents. To determine the sample, this research uses accidental sampling technique Slovin formula. Data collection through questionnaires.. This study has shown that the results of hypothesis testing t test, t known t (11.004)> t table (1.984) and Sig. (0.000) <0.05. That is experiential marketing variables significantly influence brand awarenes. t (11.082)> t table (1.984) and Sig. (0.000) <0.05. That is experiential marketing variables significantly influence buying interest.Key words : experiential marketing, brand awareness, buying interest